Lexical and Phonological Variation of Limb Terms in Cikoneng Lampung Language - Wulandari, Linda Sari; Munawarah, Sri; Lauder, Multamia R.M.T.; Humaedi, M. Alie (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
Lampung Cikoneng as a language outside its original area experiences language contact with other nearby languages, namely Sundanese and Javanese Cikoneng, Banten Province. Mutual influence may occur, both lexical and phonological variations. Through dialectological studies, this study aims to describe the form of variation in Lampung Cikoneng language on the term limb, both lexical and phonological variations, and visualize the linguistic conditions in Cikoneng Village with a language map. The research used the qualitative method. Data collection was done by interviewing 30 informants with 15 observation points. The research instrument was a questionnaire totalling 52 limb vocabularies. Data analysis was conducted using the commensurate technique. Language mapping was done using the isogloss file map. The results showed that Cikoneng Lampung language: variation with one lexical form (13.40%), variation with one lexical form but with phonological distinction (27%), and lexical variation with 2-7 lexical forms (59.60%). The Lampung Cikoneng language has been influenced by the Javanese and Sundanese languages of Cikoneng, Banten. This can be seen based on the comparison results with Lampung dialects A and O, which tend to show lexical differences. Dialect phenomena occur in some areas, where language differences do not have clear boundaries, but change gradually, reflecting the multilingual society that exists in Cikoneng Village. Based on the results of language mapping using isogloss files, Cikoneng Village is a language use area which is divided into 3 use areas, namely Lampung language use area, Sundanese language use area, and Javanese language use area. The Lampung language use area is more dominant than the 15 observation points, between observation points number 1-5 and 7, 8, and 10-13 are Lampung language use areas, while on the outskirts of observation points number 6 and 9, 14 and 15 are Sundanese and Javanese.